Expanding pregnant women’s nutrition education access via an integrated model - Rahmawati, Widya; Dewi, Mustika; Habibie, Intan Yusuf; Fahmi, Ilmia; Priambada, Swasta (Caring: Jurnal Pengabdian Masyarakat, 2024)
Ensuring proper nutrition during pregnancy is essential for fetal development and maternal well-being. The aim of this community service is to provide an integrated nutrition education guide for health workers and pregnant women, along with interesting and accurate nutrition education media for pregnant women. This community service activity is carried out through several stages, including: 1) Situation analysis; 2) Development of educational materials such as an integrated nutrition education guide for health workers, a balanced nutrition guide for pregnant women, and nutrition education videos; 3) Delivery of nutrition education through classes for pregnant women, home visits, and YouTube videos. The results of this community service activity include 1) Preparation of an integrated nutrition education guide module; 2) Preparation of a nutrition guide for pregnant women; 3) Creation of a video series on nutrition education for pregnant women; 4) Implementation of nutrition education for pregnant women; 5) Increasing the knowledge of pregnant women regarding nutrition. Furthermore, this community service activity is integrated into the Nutrition Evaluation, Intervention, and Monitoring course, providing an off-campus experience for students. By using an integrated nutrition education model that combines various approaches and communication channels, it is hoped to increase the reach of nutrition education. This will ultimately enhance the knowledge, awareness, and eating habits of pregnant women to ensure optimal maternal and fetal health. In conclusion, by using an integrated nutrition education model that combines various approaches and communication channels, it is hoped that it can increase the reach of nutrition education, which ultimately increases the knowledge, awareness and eating habits of pregnant women to ensure optimal maternal and fetal health.